Mewujudkan Siswa Sehat Melalui Edukasi Kesehatan Bijak Dalam Memilih Jajanan - Hermawan, Belya Anindia; Anggraeni, Silma Meira; Khoerunnisa, Putri Liany; Shabila, Shalza; Lubis, Novriyanti (Abdimas Universal, 2026)
This outreach activity aims to educate sixth-grade students at Muhammadiyah 2 Garut Elementary School about healthy snacks. The material covers the characteristics of healthy and unhealthy snacks, their impact on health, and how to choose good snacks. The goal is for students to be more discerning in choosing the food they consume. The material was delivered directly by students through an outreach program to the community, accompanied by lecturers. The outreach was conducted by giving instructions to fill out pretest and posttest quizzes. In addition, flyers containing information about the outreach material on healthy snacks were also distributed. With the live presentation and the completion of the pretest and posttest, it can be seen that the students' knowledge about snacks has increased. The final results showed that 96.8% of students understood healthy snacks, and 100% of students understood the importance of choosing healthy snacks. The hope of this activity is to be the first step in forming positive habits and encouraging students to be smarter in choosing the snacks they consume.